An Analysis of Figurative Languages Used in Lokamase Ceremony - Yanto Yanto; Rikardus Nong Siga (Universitas Muhammadiyah Kalimantan Timur, 2023)
The use of language in human life is very diverse, one of which is figurative language. Figurative language is the use of beautiful words with figurative language created from the author's feelings to give effect by comparing one thing with another object that is more general. The objectives of the study are to describe the types of the figurative language found in Lokamase Ceremony to identify the contextual meaning of the figurative language. This research is a qualitative research method. The method used in collecting the data related to the subject of this research is observation, interviews and documentation method. This study was conducted by collecting any relevant data and information about the topic or problem of the study from head of Lokamase and journal that are available for the analysis. The data collection used the following steps: collecting, reduction, display, and drawing conclusion and then selecting the data that used the types of figurative language. While the steps to analyze the data are identifying the types of figurative language, identifying the contextual meaning of the figurative language, and the last is interpreting the data. The result shows that found simile and hyperbole types of figurative language used in Lokamase ceremony and have their own meaning. Summing up the overall language of the figurative meanings used in the lokamase traditional ceremony is to uphold self-respect, human rights and also maintain indigenous culture.